2010
DOI: 10.1097/sla.0b013e3181bdf8ad
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antithrombin III Concentrates on Portal Vein Thrombosis After Splenectomy in Patients With Liver Cirrhosis and Hypersplenism

Abstract: These results demonstrate that low AT-III activity and further decreases in this activity are associated with PVT after splenectomy in cirrhotic patients, and that treatment with AT-III concentrates is likely to prevent the development of PVT in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 46 publications
0
83
0
1
Order By: Relevance
“…Postoperative dynamic CT should be planned approximately 1 week after splenectomy for early detection of PSVT. Kawanaka et al [24] reported that preoperative antithrombin (AT)-III activity was the most important predictive factor for PVT, and that treatment with AT-III concentrates is likely to prevent the development of PSVT. In this study, we have shown that preoperative AT-III activity was not associated with postoperative PSVT.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative dynamic CT should be planned approximately 1 week after splenectomy for early detection of PSVT. Kawanaka et al [24] reported that preoperative antithrombin (AT)-III activity was the most important predictive factor for PVT, and that treatment with AT-III concentrates is likely to prevent the development of PSVT. In this study, we have shown that preoperative AT-III activity was not associated with postoperative PSVT.…”
Section: Discussionmentioning
confidence: 99%
“…Portal thrombosis was treated with anticoagulants according to our protocol. The prevalence of portal thrombosis in patients with no prophylactic anticoagulation, with prophylactic anticoagulation using warfarin potassium, and prophylactic anticoagulation using danaparoid sodium and warfarin potassium were 33.3% (2/6 patients), 16.7% (4/24 patients), and 6.3% (1/16 patients), respectively. Bacterial infections and ascites were successfully treated with antibiotics and diuretics, respectively.…”
Section: Complications After Splenectomymentioning
confidence: 99%
“…However, it is not clear whether splenectomy can improve the overall outcome and survival of such patients. Furthermore, major life-threatening complications in such patients include overwhelming postsplenectomy infection associated with a high mortality rate and a high incidence of portal thrombosis [15,16]. Hence, the debate continues as to whether splenectomy worsens or improves patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The administration of antithrombin Ⅲ (AT-Ⅲ) could be an attractive alternative to PVT in cirrhosis. Kawanaka et al [83] demonstrated that the low AT-Ⅲ activity and further decreases in this activity are associated with PVT after splenectomy in patients with cirrhosis and that treatment with AT-Ⅲ concentrates is likely to prevent the development of PVT in these patients.…”
Section: Treatmentmentioning
confidence: 99%